1995
DOI: 10.14742/ajet.2074
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia reporting in science problem solving

Abstract: The increasing availability of CD ROM based interactive multimedia packages to support learning in science classrooms offers science teachers new pedagogical opportunities for student-centred and cooperative learning. However, many of the current products do not make full use of the existing technology in schools and even when they do they tend to constrain the student to a very limited view of information and how it can be used as part of student reporting of inquiry projects.Interactivity in many packages ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Simulations and support tools which allow: multimedia reporting are embedded in the package and are supported by several metacognitive tools for the writing process. These tools not only include details about genre but also scaffolding templates to support the learners (Harper, Hedberg, Wright and Corderoy, 1996) in constructing their own realities using the constructs and processes in the environment on a new content domain.…”
Section: An Example Of the Relation Between Metacognition And Learninmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations and support tools which allow: multimedia reporting are embedded in the package and are supported by several metacognitive tools for the writing process. These tools not only include details about genre but also scaffolding templates to support the learners (Harper, Hedberg, Wright and Corderoy, 1996) in constructing their own realities using the constructs and processes in the environment on a new content domain.…”
Section: An Example Of the Relation Between Metacognition And Learninmentioning
confidence: 99%
“…They greatly enrich the quality of the problem solving process for students by providing the student with unhindered access to act and become immersed in a real situated process. They also promote the adoption by the student of the active learner mode and in so doing support the active construction of knowledge during the process of solving a problem (Harper, Hedberg, Wright and Corderoy, 1996). A necessary skill in problem solving is the ability to collect and manipulate and analyse many different forms of data and then present them in meaningful and useful ways to any of the many different discourse communities.…”
Section: Learners Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Kenny & Schroeder (1994) reviewed the provision of note taking facilities in multimedia packages and observed that guidance on the making of effective notes was rarely provided. Harper et al (1995) expressed the fear that without such guidance, students would replicate the Downloaded by [Newcastle University] at 08:48 20 December 2014 120 C. Lawless & S. Freake failures in 'pencil and paper' notes identified by Kierwa (1987), a failure to give structure to their notes or to add further information.…”
Section: The Process Of Studymentioning
confidence: 99%